Thar ICD layout - Roy, Debjit, (SAGE knowledge. Cases., 2016)
To reduce congestion at the ports, inland container depots (ICDs) facilitates intermediate handling, storage and delivery of containers from the customer premises to the container terminals and vice versa. The design of an ICD affects the turnaround times for storage and retrieval. Further, the number of resources - such as reach-stackers - affects the throughput capacity of an ICD. Through this case, the participants should understand the ICD operations and the system design elements.